Characterization of Flavonol Inhibition of DnaB Helicase: Real-Time Monitoring, Structural Modeling, and Proposed Mechanism. (2nd October 2012) - Lin, Hsin-Hsien; Huang, Cheng-Yang
Abstract : DnaB helicases are motor proteins essential for DNA replication, repair, and recombination and may be a promising target for developing new drugs for antibiotic-resistant bacteria. Previously, we established that flavonols significantly decreased the binding ability of Klebsiella pneumoniae DnaB helicase ( Kp DnaB) to dNTP. Here, we further investigated the effect of flavonols on the inhibition of the ssDNA binding, ATPase activity, and dsDNA-unwinding activity of Kp DnaB. The ssDNA-stimulated ATPase activity of Kp DnaB was decreased to 59%, 75%, 65%, and 57%, in the presence of myricetin, quercetin, kaempferol, and galangin, respectively. The ssDNA-binding activity of Kp DnaB was only slightly decreased by flavonols. We used a continuous fluorescence assay, based on fluorescence resonance energy transfer (FRET), for real-time monitoring of Kp DnaB helicase activity in the absence and presence of flavonols. Using this assay, the flavonol-mediated inhibition of the dsDNA-unwinding activity of Kp DnaB was observed. Modeled structures of bound and unbound DNA showed flavonols binding to Kp DnaB with distinct poses. In addition, these structural models indicated that L214 is a key residue in binding any flavonol. On the basis of these results, we proposed mechanisms for flavonol inhibition of DNA helicase. The resulting information may be useful in designing compounds that target K. pneumoniae and other bacterial DnaB helicases.